Mosaic rearrangement of chromosome 18: Characterization by FISH mapping and DNA studies shows trisomy 18p and monosomy 18p both of paternal origin - Oner, Guner; Jauch, Anna; Eggermann, Thomas; Hardwick, R.; Kirsch, Stefan; Schiebel, Katrin; Rappold, Gudrun; Robson, Lisa; Smith, Arabella (American journal of medical genetics, 2000)
Structural abnormalities of chromosome 18p mainly consist of isochromosomes of the short arm, which result in tetrasomy 18p. Trisomy 18p is much rarer, and less well characterized. We report on a 12-year-old girl with minor facial anomalies, delayed development, abnormal hands, atopic dermatitis, and hearing loss. She was mosaic for two abnormal cell lines in peripheral blood. In 90% of cells, a dicentric chromosome with duplication of the whole short arm of chromosome 18 resulted in trisomy 18p; 10% of cells had monosomy 18p, arising from a t(14;18)(p11;q11). FISH mapping, with multiple region specific and locus specific probes from the short and long arm of chromosome 18, showed that the structure of the dicentric chromosome 18 was 18pter→18q23::18q11→18pter. DNA polymorphisms for chromosome 18 showed that the abnormalities of chromosome 18 were paternal in origin. Combining all results, we could link the trisomy 18p and monosomy 18p to a common origin via a complex series of events in an early mitosis. Am. J. Med. Genet. 92:101-106, 2000. © 2000 Wiley-Liss, Inc.
Gesehen am 25.03.2021